A aposta na dimensão de convivialidade: prevenção e saúde mental no cuidado com a primeira infância - Teixeira, Bruna Caixeta Alves (2022)
This research aimed to weave constructions regarding the care given to early infancy in a public context of mental health, asking the following question: is it possible to think of a proposition of psychoanalytic work with children that lays, fundamentally, on the dimension of conviviality as a prevention strategy? To offer possible answers to this question, a methodological path was followed supported by the ethics of psychoanalysis. Such path guided listening and instrumentalized transfer regarding the texts chosen to compose the general discussion, appointing the aspects that could be better elucidated. The path treaded in this work was driven by the narrative of an experience in a public service for early infancy care. From there, some notes were made on the performance of psychoanalysis in the sphere of public health, considering historical factors that laid the foundations for a psychoanalysis of children conducted in this context. A central element that supports the discussions around the theme is the proposition by Françoise Dolto, that argues for the creation of the Maison Verte, a welcoming space for the transition from the family environment to the school environment. The logic of Dolto's work helps consider a position that listens to the multiple effects of infancy and, thus, that the subjective dimension is not silenced. Children, in coexistence with their caregivers and all other individuals who attend such space, can have an environment conducive to their development; and from the mediation by language, the affective variations in play can be followed. In this direction, it was possible to make considerations about the role of the analyst and the role of the institution from a logic of care and reception for early infancy, focusing on the promotion of conviviality as a prevention strategy. Such prevention does not merely consider the avoidance of suffering, but it also provides a place of reception and care so that possible solutions in the face of suffering and the difficulties of living can be built together. The approach of the dimension of conviviality opens the way for the recognition of what the subject can become in its singularity, building possibilities of existence and transformation.